Rural schools of São João do Sabugi/RN (1954) - Aline de Medeiros Fernandes (Pesquisa e Ensino, 2020)
The purpose of this text is to present the mapping of primary public schools in rural areas of São João do Sabugi, in Rio Grande do Norte and the model that was implemented for teaching demands. The theoretical and methodological framework relates to the premises of hybrid thematic Oral History, to consider documentary analysis. The expository movement of the text started from the contextualization of the object and conceptualization of the unitary school model. The analysis has shown that the rural schooling from São João do Sabugi subsidized by public resources was born in 1954 by virtue of Municipal Law No. 63, in April 2, 1954 (although schools offered by the state were identified, the city would maintain them without proper legislation regarding state creation) and that the teachers dedicated to teaching in the context of family and personal life.